Glitchy Sextech: Failure, Frustration, and Fragility in Networked Sex Toys. - Sundén, Jenny; Stardust, Zahra; Albury, Kath (Somatechnics, 2026)
Sextech devices offer new opportunities for sexual exploration, learning, and play. In Cindy Gallop's (2015) influential definition of sextech as technologies 'designed to enhance, innovate and disrupt in every area of human sexuality and human sexual experience', an almost revolutionary power to transform sex is at the forefront. But sextech is also inherently glitchy as apps, platforms, and connections are bound to fail or break, making interruption and stuckness an inevitable part of the intimate infrastructures of networked toys. While not unique to technologies of sex, this fragility of digital technologies is especially interesting in a context where technological and sexual norms and vulnerabilities intersect. Interweaving research on intimate infrastructures and queer theory, and especially focusing on discussions of failure and glitch, we explore how neoliberal norms of success have become entangled with sexual norms in sextech configurations. Using marketing language by leading companies for networked sex toys as an analytical backdrop, we build on 25 interviews with sexual and gender diverse sextech users in Australia and Sweden to discuss what it means to integrate less than seamless, stable, and user-friendly devices into sexual lives and routines. We understand networked sextoys as infrastructural in how they prop up, extend, but also reorganise intimate lives. The discussion of technological failure in science and technology studies has moved from a focus on failure as exception or accident which reveals underlying norms and structures, to an understanding of failure as one of the key conditions of neoliberal capitalism, embedded in everyday media habits. What can we learn about sex and tech by paying attention to how digital technologies are always fragile and unreliable? And what does a focus on networked sextech add to discussions of intimate digital infrastructures more broadly, including a queer and decolonial critique?